The tribological performance of nano-activated carbon as solid additives in modified calophyllum inophyllum based-metalworking fluid - Zamri, Zubaidah; Abdul Sani, Amiril Sahab; Abd Aziz, Radhiyah; Sabri, Ainaa Mardhiah; Talib, Norfazillah
Biolubricants have attracted attention in today’s market as a new alternative to commercial lubricants due to their environmentally friendly and renewable properties. The refinement of bio-lubricants has improved their tribological and physical properties. However, to optimize the performance of lubricants when machined under high-temperature conditions, additives must be added to the lubricant. In this study, the tribological properties of modified Calophyllum inophyllum (MTO) oil combined with nano-activated carbon (NAC) as additives were investigated using the four-ball wear test method. This bio-lubricant consists of modified Calophyllum inophyllum oil in combination with NAC at concentrations of 0.01, 0.025, and 0.05 wt%. The coefficient of friction for the balls and their wear diameter are evaluated and compared. The kinematic viscosity and viscosity index of MTO were tested according to ASTM standards. The results show that a lubricant with added NAC is more effective in reducing wear and friction than a bio-lubricant without nanoactivated carbon. The bio-lubricant combined with NAC reduced the wear diameter of the lubricated balls compared to the bio-lubricant without additives. The nanoadditives have converted the sliding effect into a ball-bearing effect between the interfaces of the balls, creating a better oil protective film that helps form a gap between the mating surfaces during tribological testing